Analisis C3 Framework Kitab Parukunan Melayu Besar Bab Haji Karya Haji Abdurrasyid Banjar - Sri Maulida; Sukarni Sukarni; Muhammad Hanafiah (Cakrawala: Jurnal Studi Islam, 2019)
The Book of Parukunan is a book that is very popular among Malay people. The study is aimed to find out the writing setting of the jurisprudence book of Parukunan Melayu Besar, Hajj chapter by Haji Abdurrasyud Banjar. The author will discuss the Historical setting using the College, Career, and Civic Life (C3) Framework with a qualitative descriptive approach. The results showed that in the year of writing the Book, the Industrial Revolution was taking place where there were massive changes in agriculture, manufacturing, mining, transportation, and technology and had a profound impact on social, economic, and cultural conditions. The existence of agrarian reforms that resulted in private investment flowing into the Dutch East Indies making trade easier. Furthermore, there are developments in the export-import market so that many ships come to Banjarmasin making it easier for pilgrimage journeys. Other than that, the number of office and warehouse developments indicate an improved economic condition so that people who are economically capable can make the pilgrimage easily